MEREFLEKSIKAN IMAGO DEI DALAM PELAYANAN HAMBA TUHAN DI ERA SOCIETY 5.0 - Christianto Christianto; Matouosa Tafonao; Joseph Yahuda; Rikky Nelson; Maria Patricia Tjasmadi (TEMISIEN: Jurnal Teologi, Misi, dan Entrepreneurship, 2022)
The meeting point between the Industry 4.0, society 5.0, and the Covid-19 pandemic has forced churches to surpass conventional time and space. The attempt of adopting and utilizing various virtual means has creatd a wave of virtuangelism to voice the love of Christ. The voices of truth uploaded to the cyberspace has made evangelists feel free and liberated in sharing their thoughts. Unfortunately, virtuangelism is increasingly stained by false rhetoric. Evangelist figures who are supposed to spread good news, spreads hate speech instead or are busy competing for subscribers. Other triggers are the manifestation of the Dunning Kruger effect and the personal wounds of the evangelists. This phenomenon is more prominent in Society 5.0. Through virtual data analysis, the study of the Bible, supported by various theories, it is hoped that this study can pierce through the irrational “Rational Rhetoric” in Society 5.0. This research is highly important so that the future generations believe not in artificial intelligence more than the truth of God. Transformative changes towards the understanding of the will of God is sure to happen if the rational Christian character, in accordance to the Bible, is restored. The Godly Christian rationality, according o the bible, is that all parts of society and church is hoped to have the same vision and mission to rid irrational “Rational Rhetoric” in society 5.0Keywords : Irrational Rational,  virtual space, society 5.0